An Optimized Method for Automated Stadium Attendance Management System - Bari’ah Mosman, Asnorul; A. Mostafa, Salama; Mustapha, Aida; Ubaidah Shamsudin, Abu; Ahmed Jubair, Mohammed; Hamid Hassan, Mustafa (International Journal of Engineering and Technology, 2019)
In recent times, football and football playersâ€™ popularity is increasingly rising which make the football stadium increasingly full of supporters from both the home and opposition teams. However, the management of the stadium attendance still applies conventional methods, which results that the audiences might be dissatisfied with the attendance method. This paper proposes an optimized method for the management of the stadium attendance. The implementation of the method applies a prototype methodology to develop a systematic and efficient Automated Stadium Attendance Management (ASAM) system. In addition, communications technology of smartphones is used to scan barcodes on tickets and dismantle the data to the system. This work is meant to help stadium workers to efficiently manage the attendance of audiences. The test results show that the system successfully retrieves, and processes optimized data and information of the spectators and efficiently manages the stadium attendance.Â